How to Recruit, Support, and Retain Speech-Language Pathologists in Public Schools. Issue 3 (May 2022) - Farquharson, Kelly; Therrien, Michelle; Barton-Hulsey, Andrea; Brandt, Ann F.
Over the past two decades, there has been a persistent shortage of qualified speech-language pathologists (SLPs) across the United States. This shortage is predicted to continue, as data reported by the American Speech Language Hearing Association (ASHA) from the US Bureau of Labor Statistics indicates that there will be a 27% increase in job openings through the year 2028. In some states, the shortage has led to service provision from individuals without a background in speech-language pathology and/or without speech-language pathology certification and licensure. Speech and language services that are delivered by unqualified personnel may lead to inadequate time devoted to therapy—either too much, or too little—which is ultimately unethical, illegal, and expensive. However, there is a real issue at hand for school leadership—and that is: How to recruit, support, and retain highly qualified SLPs? In the current tutorial, we will provide evidence-based action steps for how and why to recruit, support, and retain certified and licensed SLPs. Specifically, we discuss the qualifications of the SLP, roles and responsibilities of school-based SLPs, caseload versus workload considerations, various service delivery models, and a review of SLP job satisfaction research. Throughout the tutorial, we will provide concrete and evidence-based ideas for school leadership to consider when recruiting, supporting, and retaining SLPs.